Mechanism underlying the correlation between the warming-wetting of the Qinghai-Tibet Plateau and atmospheric energy changes in high-impact oceanic areas - Na Dong; Xiangde Xu; Renhe Zhang; Chan Sun; Wenyue Cai; Runze Zhao (npj Climate and Atmospheric Science)
Abstract The powerful thermal driving force of the Qinghai-Tibet Plateau (QTP) exerts a significant influence on weather, climate, and environmental processes in Asia and across the globe. This paper investigates the causes of climate change on the QTP from the perspective of global atmospheric energy transport and water cycle. During summer, a “hollow energy pool” has been discovered in the troposphere, with its energy center located above the QTP, the “Asian water tower”. Our study indicates that the QTP serves as a critical “window” for the global transport of water vapor and energy. Since 1991, the total atmospheric energy (TAE) and precipitation in the warming-wetting region of the QTP (central and northern plateau) have exhibited interdecadal growth. Furthermore, the TAE of the plateau is closely linked to the TAE and water vapor of oceans at mid-low latitudes, and even in the southern hemisphere, the increased precipitation in the warming-wetting region of the plateau has been mainly regulated by the atmospheric energy and water vapor transport structures over the equatorial western Pacific, southwestern Pacific, and southern Indian Ocean, we further reveal the energy transport channel from the warming oceanic areas of the southern and northern hemispheres to the QTP. This study deepens the novel understanding of atmospheric energy accompanying water vapor transport in the southern and northern hemispheres, which is of significant importance for understanding the responses of energy and water cycle in the warming-wetting of the QTP and global climate change.